Plasma Biomarkers of Alzheimer's Disease Are Associated with Physical Functioning Outcomes Among Cognitively Normal Adults in the Multiethnic HABS-HD Cohort. Issue 1 (18th August 2022) - O'Bryant, Sid E; Petersen, Melissa; Hall, James R; Large, Stephanie; Johnson, Leigh A
Abstract: In this study, we examined the link between plasma Alzheimer's disease (AD) biomarkers and physical functioning outcomes within a community-dwelling, multiethnic cohort. Data from 1 328 cognitively unimpaired participants ( n = 659 Mexican American and n = 669 non-Hispanic White) from the ongoing Health & Aging Brain Study—Health Disparities (HABS-HD) cohort were examined. Plasma AD biomarkers (amyloid beta [Aβ]40, Aβ42, total tau [t-tau], and neurofilament light chain [NfL]) were assayed using the ultra-sensitive Simoa platform. Physical functioning measures were the Timed Up and Go (TUG) and the Short Physical Performance Battery (SPPB). Cross-sectional linear regression analyses revealed that plasma Aβ 40 ( p < .001), Aβ 42 ( p = .003), and NfL ( p < .001) were each significantly associated with TUG time in seconds. Plasma Aβ 40 ( p < .001), Aβ 42 ( p < .001), t-tau ( p = .002), and NfL ( p < .001) were each significantly associated with SPPB Total Score. Additional analyses demonstrate that the link between plasma AD biomarkers and physical functioning outcomes were strongest among Mexican Americans. Plasma AD biomarkers are receiving a great deal of attention in the literature and are now available clinically including use in clinical trials. The examination of AD biomarkers and physical functioning may allow for the development of risk profiles, which could stratify a person's risk for neurodegenerative diseases, such as AD, based on plasma AD biomarkers, physical functioning, ethnicity, or a combination of these measures prior to the onset of cognitive impairment.